2022
DOI: 10.1002/cft2.20154
|View full text |Cite
|
Sign up to set email alerts
|

Effects of drip irrigation and cultivation methods on establishment of seeded tall fescue

Abstract: Subsurface drip irrigation (SDI) may save water but its effectiveness in establishing seeded turfgrass across different soil types and climates requires further investigation. This study was conducted in fine‐textured soils near Manhattan, KS. Our objectives were to investigate establishment of seeded tall fescue [Schedonorus arundinaceus (Schreb.) Dumort.] using: (a) SDI, aboveground drip irrigation (AGD), and overhead sprinkler irrigation (OH); and (b) core aeration vs. verticutting for seedbed preparation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The visible atmospherically resistant index (VARI; Table 1), which uses green and red wavebands in the visible spectrum and was developed to reduce atmospheric effects (Gitelson et al, 2002), was strongly correlated with PGC of turfgrass under drought stress in a sUAS study (Zhang et al, 2019b). The dark green color index (DGCI) derived from sUAS RGB images was highly correlated with sUAS measurements of NDVI (r = 0.85 to 0.96; under different N fertilization regimes), which implies DGCI might be used in lieu of NDVI to detect droughtinduced leaf firing when spectral sensors that measure NIR reflectance are not available (Caturegli et al, 2019); strong relationships between NDVI and PGC in turfgrass have been reported by others using sUAS-based measurements (Bach et al, 2022a) and ground-based measurements (Bell et al, 2002;Bremer et al, 2011b).…”
Section: Sensormentioning
confidence: 86%
See 2 more Smart Citations
“…The visible atmospherically resistant index (VARI; Table 1), which uses green and red wavebands in the visible spectrum and was developed to reduce atmospheric effects (Gitelson et al, 2002), was strongly correlated with PGC of turfgrass under drought stress in a sUAS study (Zhang et al, 2019b). The dark green color index (DGCI) derived from sUAS RGB images was highly correlated with sUAS measurements of NDVI (r = 0.85 to 0.96; under different N fertilization regimes), which implies DGCI might be used in lieu of NDVI to detect droughtinduced leaf firing when spectral sensors that measure NIR reflectance are not available (Caturegli et al, 2019); strong relationships between NDVI and PGC in turfgrass have been reported by others using sUAS-based measurements (Bach et al, 2022a) and ground-based measurements (Bell et al, 2002;Bremer et al, 2011b).…”
Section: Sensormentioning
confidence: 86%
“…However, recent sUAS studies have indicated moderate to strong correlations between ground-and sUAS-based measurements of spectral reflectance in turfgrass. Correlations between ground-and sUAS-based NDVI ranged from r=0.63 to 0.97 in a number of turfgrass studies (Caturegli et al, 2016;Hong et al, 2019b;Zhang et al, 2019b;Friell and Straw, 2021;Bach et al, 2022aBach et al, , 2022b. Hong et al (2019b) also reported strong correlations (r=0.69 to 0.87) between sUAS-based broadband NIR (about 680-780 nm) and ground-based narrowband NIR (around 780 nm) in drought-stressed turfgrass.…”
Section: Relationships Between Aerial and Ground-based Measurementsmentioning
confidence: 97%
See 1 more Smart Citation